Monitoramento das irregularidades ionosféricas e cintilação dos sinais GNSS: em tempo real e pós-processado - Pereira, Vinícius Amadeu Stuani [UNESP] (2015)
Ionosphere is one of the largest sources of systematic errors in positioning by GNSS (Global Navigation Satellite System), due to observables be affected by several ionospheric conditions resulting from changes of space weather. Brazil, located in the tropical region, is one of the countries that suffer the effects of the ionosphere, especially those from the Equatorial Ionization Anomaly (EIA), ionospheric irregularities and scintillation of GNSS signals. Develop new algorithms and enhance existing ones, in order to minimize the effects of the ionosphere, is one of the main goals of the Space Geodesy, due to increased solar activity in the triennium 2013-2014-2015. Several strategies can be used in order to minimize the ionospheric effects, either through ionospheric models, or from IONEX files as well as using the ion-free, unless each of these strategies with their respective levels of attenuation. Regarding the monitoring of the ionosphere the situation is different. The amount of instruments dedicated to the study of ionospheric layer is reduced in the Brazilian context. The few ionosondes, optical imagers and specialized geodetic receivers in providing ionosphere-related parameters throughout the territory are insufficient for monitoring and detailed analysis of ionospheric irregularities and scintillation. In this context was developed a scientific application (Ion_Index) in order to estimate indicators of irregularities levels of the ionosphere and scintillation of GNSS signals for the Brazilian territory in real time and post-processed using the existing infrastructure of active public networks of GNSS...